Molecular Dynamics Study of the Interaction of Arginine with Phosphatidylcholine and Phosphatidylethanolamine Bilayers - Herrera, Fernando Enrique (2012)
In this work, the differential interaction of zwitterionic arginines with fully hydrated dimyristoylphosphatidylcholine (DMPC) and dimyristoylphosphatidylethanolamine (DMPE) bilayers was analyzed by molecular dynamics simulations. In both systems arginine binds to lipids with the carboxylate moiety oriented towards the aqueous phase, in agreement with previous experimental determinations of zeta potential of DMPC and DMPE liposomes.The guanidinium groups are found at different depths within the bilayers indicating that some arginines are buried, especially in DMPE. We observe, in the DMPE system, that the strongest interaction occurs between the guanidinium group and the carbonyl oxygen of the lipid. In the case of DMPC membranes, the strongest interaction is found between the guanidinium groups of the arginines and the phosphate groups of the lipids. Unexpectedly, arginine zwitterions are hardly stabilized through the creation of hydrogen bonds (HB), either with water or with polar groups of the lipids. The mechanisms of interaction seem to be different in both membranes. In DMPE bilayers, arginines insert by breaking the inner HB network of the polar head groups, consequently increasing the occupied area per lipid molecule. In the DMPC bilayers the arginines insert by replacing the already present water molecules within the membrane, without significant effects on the area per lipid.